Efecto de la lesión de nervio facial sobre la plasticidad en la sinapsis comisural CA3-CA1 de hipocampo de rata. (2019)
The experiments described here were conducted at the Behavioral Neurophysiology Laboratory of Medicine School, Universidad Nacional de Colombia. The goal of this research was to describe the evolution of changes in synaptic plasticity of hippocampal CA3- CA1 commisural circuit, after facial nerve injury in rats. For such end, irreversible injury on the mandibular and buccal branches of the right facial nerve (FNI, facial nerve injury) were made. This injury provoked an irreversible paralysis of the facial’s lower third of experimental animals. It means, the facial nerve injury produced paralysis that lead to the impossibility of active movement of the vibrissae of the injured side. The amplitudes of field excitatory potentials (fEPSP) were recorded in vivo in hippocampal CA1 region (contralateral to injury) after electrical stimulation of crescent amplitude in the CA3 region (ipsilateral to injury), at 1 (1D, n = 3), 3 (3D, n = 3), 7 (7D, n = 4) or 21 (21D, n = 2) days post-lesion. The values obtained were compared with a sham-surgery group (control, n = 4). After the FNI we reported that all the experimental groups were able to potentiate the CA3- CA1 synapsis, at least by one hour after high-frequency stimulation protocol (HFS); however, we found a significant decrease in this potentiation in 3D, 7D and 21D groups, compared with the control group. Short-term plasticity was analyzed with a pair-pulse stimulation through the comparison of the responses to two sequential identical stimuli, separated by an inter-stimuli interval of 100 ms. The ratio between the response of the second stimulus/response to the first stimulus (R2/R1, registered in CA1 after stimulation in contralateral CA3) was evaluated in all experimental groups. It was found that the control and all the experimental groups were able to facilitate their response to a second stimulus in regard to the first one. Nonetheless, the facilitation was significantly diminished in 3D and 7D groups when compared to the control group. Furthermore, after a HFS, both control and 3D groups diminished significantly their facilitation ratio.